Articolo individuante o generico? - Cignelli, L. (Liber Annuus, 2006)
Abstract Some passages of the NT are analyzed in which the article may have either individual or generic meaning; the consequences for exegesis depending on whether we choose either one or the other are highlighted and attention is called for in the interpretation of texts.